Peningkatan Pemahaman Peran Keluarga dalam Pendidikan dan Pengasuhan Anak bagi Keluarga Penerima Manfaat PKH Jakarta Utara: Pengabdian - Suyuti; Devi Septiandini; Ike Arriany; Meilien Mocharom; Putri Wantini (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service program aims to improve the understanding of beneficiary families of the Family Hope Program (PKH) about the importance of education and childcare patterns in North Jakarta. The implementation method uses a participatory approach through counseling, discussions, simulations, and direct mentoring involving the community service team, PKH facilitators, and PKH beneficiary families. This activity begins with observations and interviews, followed by counseling sessions on education and positive parenting patterns, as well as mentoring in the preparation of family action plans for accompanying children's learning. The results of the activity show a significant increase in family understanding of the importance of education, the implementation of positive parenting patterns, and the formation of new behavioral patterns such as the preparation of children's study schedules and regular mentoring. This activity also succeeded in building synergy between PKH facilitators and families in monitoring the development of education and childcare on an ongoing basis.. This activity is expected to become a good practice that can be replicated in PKH programs in other regions as an effort to break the chain of poverty through education and strengthening the role of the family.